2006
DOI: 10.1111/j.1365-2249.2006.03171.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed inflammatory/regulatory cytokine profile marked by simultaneous raise of interferon-γ and interleukin-10 and low frequency of tumour necrosis factor-α+ monocytes are hallmarks of active human visceral Leishmaniasis due toLeishmania chagasiinfection

Abstract: Mixed inflammatory/regulatory cytokine profile marked by simultaneous raise of interferon-g and interleukin-10 and low frequency of tumour necrosis factor-a + monocytes are hallmarks of active human visceral Leishmaniasis due to Leishmania chagasi infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
103
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 27 publications
15
103
0
5
Order By: Relevance
“…Although some studies evaluating cytokines in serum samples have either not detected or found low concentrations of 69,70 , other studies have produced conflicting results. IFN-g was detected in 17 of 44 patients in Iran 2 and in 13 of 15 patients in Brazil 20 ; in addition, high levels have been confirmed in patients in Asia, Europe, Africa, and Brazil 9,15,31,32,50,52 . These differing results are most likely not related to the selected patient groups or to the Leishmania species involved, but rather to the samples that were analyzed.…”
Section: Immunoactivation In Lymphoid Organsmentioning
confidence: 93%
See 1 more Smart Citation
“…Although some studies evaluating cytokines in serum samples have either not detected or found low concentrations of 69,70 , other studies have produced conflicting results. IFN-g was detected in 17 of 44 patients in Iran 2 and in 13 of 15 patients in Brazil 20 ; in addition, high levels have been confirmed in patients in Asia, Europe, Africa, and Brazil 9,15,31,32,50,52 . These differing results are most likely not related to the selected patient groups or to the Leishmania species involved, but rather to the samples that were analyzed.…”
Section: Immunoactivation In Lymphoid Organsmentioning
confidence: 93%
“…It has also been found to be important in susceptibility to visceral leishmaniasis 30,49 . It has been detected in different samples of human visceral leishmaniasis: as mRNA in bone marrow 36 , lymph node 27 , and spleen 38 aspirates and at high levels in serum 1,2,15,40,50,52,63,69 ; for further information see 51 . As mentioned earlier, the possible effect of IL-10 on the production of, or proliferation of IFN-g producing cells 11,28 may not be important given the high activation of the immune response in lymphoid organs during active disease.…”
mentioning
confidence: 99%
“…It has also been postulated that gut parasitization by Leishmania amastigotes accelerates the mucosal damage associated with HIV-1 infection, increasing the levels of microbial translocation into the bloodstream, causing a systemic proinflammatory response and increasing immune activation [17][18][19][20][21][22][23][24]. Furthermore, higher T-helper type 2 (Th2) cytokine production has been observed in peripheral blood mononuclear cells (PBMCs) from coinfected patients [12,25].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been postulated that gut parasitization by Leishmania amastigotes accelerates the mucosal damage associated with HIV-1 infection, increasing the levels of microbial translocation into the bloodstream, causing a systemic proinflammatory response and increasing immune activation [17][18][19][20][21][22][23][24]. Furthermore, higher T-helper type 2 (Th2) cytokine production has been observed in peripheral blood mononuclear cells (PBMCs) from coinfected patients [12,25].To date, most studies of VL/HIV coinfection have been carried out in patients with active HIV-1 replication and/or active VL, and there are no studies comparing VL/HIVcoinfected patients and other HIV-1-infected patients with similar immunological alterations but without Leishmania coinfection, such as immunodiscordant patients [26,27]. Thus, we designed a study to investigate how VL could alter immunological parameters in HIV-1-infected patients with virological suppression, and to determine the factors that could explain the impaired immune response and frequent relapses in coinfected patients, in comparison with HIV-1-infected patients with IDR and also patients who had an adequate, concordant immunological response (CR) to cART.…”
mentioning
confidence: 99%
“…However, the basal levels of these cytokines have been detected in asymptomatic cases from Brazil, a finding that requires Key words: cytokines -visceral leishmaniasis -clinical forms further investigation (Peruhype-Magalhães et al 2006). A significant reduction in these cytokines, particularly a decline in IFN-γ, which has been indicated to be a reliable marker of the cured disease, has been observed in patients after treatment of VL (Caldas et al 2005, Ansari et al 2006.…”
mentioning
confidence: 99%